SOCIAL CRITICISM OF ASIAN CULTURE IN FILM â€œTO ALL THE BOYS I'VE LOVED BEFOREâ€ WITH BARTHESâ€™ POPULAR CULTURE THEORY - Kurnia Dwi Alfianto; Altobeli Lobodally (Jurnal Komunikasi dan Bisnis, 2020)
Mass media often perceived Asian Culture as a powerless culture. Just like in To All the Boys I’ve Loved Before film that criticizing Asian culture. This study aimed to unveil the social criticism of Asian culture depicted on To All the Boys I’ve Loved Before. This qualitative study using Popular Culture Theory with Roland Barthes’ semiotic analysis method by three elements of analysis (denotation, connotation, and myth). This study unveiled that the social criticism of Asian culture is linked with its collectivistic culture and interdependent characteristic, also overly-controlled Asian parents. This study also found the shift and consolidation of myth of Asian culture. Other than that, social criticism of Asian culture depicted on the film is the form of low culture and used as the asset to gain profit. Therefore, Asian culture has been marginalized and wrapped as a form of commercialized culture. Keywords: asian culture, popular culture, film, social criticism, semiotics